Glymphatic System Impairment in Alzheimer's Disease and Idiopathic Normal Pressure Hydrocephalus. Issue 3 (March 2020) - Reeves, Benjamin C.; Karimy, Jason K.; Kundishora, Adam J.; Mestre, Humberto; Cerci, H. Mert; Matouk, Charles; Alper, Seth L.; Lundgaard, Iben; Nedergaard, Maiken; Kahle, Kristopher T.
Abstract : Approximately 10% of dementia patients have idiopathic normal pressure hydrocephalus (iNPH), an expansion of the cerebrospinal fluid (CSF)-filled brain ventricles. iNPH and Alzheimer's disease (AD) both exhibit sleep disturbances, build-up of brain metabolic wastes and amyloid-β (Aβ) plaques, perivascular reactive astrogliosis, and mislocalization of astrocyte aquaporin-4 (AQP4). The glia–lymphatic (glymphatic) system facilitates brain fluid clearance and waste removal during sleep via glia-supported perivascular channels. Human studies have implicated impaired glymphatic function in both AD and iNPH. Continued investigation into the role of glymphatic system biology in AD and iNPH models could lead to new strategies to improve brain health by restoring homeostatic brain metabolism and CSF dynamics. Highlights: iNPH constitutes ∼10% of the 50 million people currently diagnosed with a dementia-related disorder. This is expected to exceed 150 million by 2050. iNPH and AD share multiple clinical and pathologic features such as Aβ deposition, cerebrovascular inflammation, impaired localization of perivascular AQP4, and sleep disturbances. Although glymphatic system dysfunction has been extensively studied in AD, it has not yet been thoroughly examined in model systems of iNPH and other types of hydrocephalus. Several studies analyzing brain magnetic resonance imaging of human iNPH patients have shown reduced perivascular influx and efflux of intrathecally injected contrast agent compared to controls, suggesting impairment of glymphatic function iNPH. The relationship between glymphatic system function and iNPH requires further investigation because it may point toward identifiable risk factors or therapeutic targets.